1999
DOI: 10.1152/jappl.1999.87.3.999
|View full text |Cite
|
Sign up to set email alerts
|

Negative interstitial pressure in the peritendinous region during exercise

Abstract: In the present study, tissue pressure in the peritendinous area ventral to the human Achilles tendon was determined. The pressure was measured during rest and intermittent isometric calf muscle exercise at three torques (56, 112, and 168 Nm) 20, 40 and 50 mm proximal to the insertion of the tendon in 11 healthy, young individuals. In all experiments a linear significant decrease in pressure was obtained with increasing torque [e.g., at 40 mm: -0.4 +/- 0.3 mmHg (rest) to -135 +/- 12 mmHg (168 Nm)]. No significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…Thus, these mechanical stimuli may lead to an increased vascularity and dilation of blood vessels within the Achilles tendon. Indeed, Langberg et al (1999b) reported that a negative tissue pressure was caused in the peritendinous space around the Achilles tendon during exercise, and concluded that negative tissue pressure could lead to a fluid shift. In addition, Boesen et al (2006) observed Doppler activity in nine of ten subjects after repetitive loading (5-km running), and suggested that the relative hyperemia seen after exercise is a physiological response.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these mechanical stimuli may lead to an increased vascularity and dilation of blood vessels within the Achilles tendon. Indeed, Langberg et al (1999b) reported that a negative tissue pressure was caused in the peritendinous space around the Achilles tendon during exercise, and concluded that negative tissue pressure could lead to a fluid shift. In addition, Boesen et al (2006) observed Doppler activity in nine of ten subjects after repetitive loading (5-km running), and suggested that the relative hyperemia seen after exercise is a physiological response.…”
Section: Discussionmentioning
confidence: 99%
“…In the in vivo situation it is also possible that pressure may influence to what extent force is transmitted between adjacent fascicles. In the human Achilles tendon it has been shown that loading creates negative pressures around the tendon (Langberg et al, 1999), and therefore likely within the tendon per se. However, how this influences the mechanics of force transmission between fascicles remains unknown, and this variable was unaccounted for in the present model.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of a significant temperature effect is further supported by the fact that the elevation in intramuscular temperature associated with 40 min of running does not appear to influence the passive resistance of the human muscle–tendon complex (Magnusson et al 2000). Fluid shifts within the tendon are another possible explanation since it has been shown that in humans, in vivo , there is a marked negative tissue pressure in the peritendinous space around the Achilles tendon during exercise (Langberg et al 1999 a ).…”
Section: The Effect Of Repeated Loading On the Mechanical Properties mentioning
confidence: 99%